Analysis of passengers perception on public transport facilities at Kota Kinabalu Sabah - Zulkitti Madisibi; Lillian Gungat; Mohd Azizul Bin Ladin (Faculty of Science and Natural Resources, 2021)
Quality of public transport plays a major role in growing the demand for public transportation in Kota Kinabalu, Sabah. Analysis of passenger perceptions of public transport facilities in Kota Kinabalu was studied by interview methods and survey questions. The respondents were consist of public bus users and operators. The collected data were analysed using SPSS 26 and thematic analysis. As a result of the findings of the analysis made on the cleanliness of public transport, most passengers stated bad because most public transport are in a relatively old and old condition. In addition, the perception of passengers also on the environment of bus terminals and bus stops, passengers stated that the environmental conditions of these two facilities are unsatisfactory.